A multicenter, randomized, double‐blind clinical study to evaluate the efficacy and safety of a new monophasic hyaluronic acid filler with lidocaine 0.3% in the correction of nasolabial fold. (1st February 2017) - Suh, Joon Hyuk; Oh, Chang Taek; Im, Song I; Lim, Jung Soo; Kim, Beom Joon; Lee, Jong Hun
Summary: Background: Many new brands of hyaluronic acid (HA) fillers are being introduced, but comparative research on the characteristics of similar products is limited. Objective: To test the efficacy, tolerability, and safety of a HA filler with lidocaine, Dermalax implant plus™ (Across), which is used for correcting nasolabial folds (NLFs), and to compare the performance of that of Restylane Sub‐Q ® (Q‐Med). Methods: A total of 52 subjects with visible NLFs were enrolled in this randomized, multicenter, patient/evaluator‐blind, active‐controlled, matched‐pair clinical study. Each subject was injected with Dermalax implant plus™ in one NLF and Restylane Sub‐Q ® in the other. All participants were reassessed for cosmetic changes at 2, 8, 12, 16, and 24 weeks. Wrinkle severity was rated using the 5‐point Wrinkle Severity Rating Scale (WSRS). Results: At week 24, the mean improvement in the WSRS compared to baseline was 1.06±0.54 for the PLUS side and 0.69±0.58 for the Sub‐Q side (week 2: 1.67±0.58 and 1.21±0.67, week 8: 1.60±0.63 and 1.23±0.65, week 12: 1.58±0.61 and 1.15±0.61, week 16: 1.02±0.54 and 0.60±0.53). Average values of pain evaluated by self‐assessment 100‐mm VAS score within 30 minutes after the procedure in the PLUS and Sub‐Q groups were 14.65±16.23 and 38.29±27.27, respectively. Both fillers were well tolerated, and adverse reactions were mild. Conclusion: We confirmed that the monophasic HA containing pre‐incorporated lidocaine (PLUS) is not inferior to well‐studied biphasic HA (Sub‐Q) in correcting to severe nasolabial folds for 24 weeks and less painful than biphasic HA not containing lidocaine.